Teknologi Proses Ekstraksi Tokoferol dari Rumput Laut Sebagai Sumber Vitamin E pada Sabun Mandi - Yuni Adiningsih (Balai Riset dan Standardisasi Industri Samarinda, 2016)
East Kalimantan province has developed seaweed aquaculture in particular, especially in the area of Bontang, East Kutai, Berau and Nunakan. The seaweed potential is quite large at around 170,000 tonnes / year (Department of Fisheries 2012). Like land plants in general, seaweed also has chlorophyll or other pigment colors. In addition, seaweed contains vitamin A and vitamin E (Sunarto, 2003). Vitamin E prevents lipofuscin, oxidized fats trigger premature aging of the skin. The purpose of this study was to determine the types of seaweed extraction method to obtain Euchema cotonii seaweed extract with vitamin E in the form of Tocopherol. Furthermore seaweed extract is added as an additive into the soap as much as 2%. Extraction technique used is the method of cold crystallization with methanol. Seaweed extract were tested using HPLC method and obtained tocopherol content 0.17 to 1.14 IU, free fatty acids 3.54%-4.42%, peroxide 4.05%-4.15%. The addition of seaweed extract as a source of tocopherols did not affect the quality of the soap produced according to standard SNI 06-3532-1994 (SNI soap)